2012
DOI: 10.5935/1678-9741.20120005
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroides intravenosos no perioperatório reduzem a incidência de fibrilação atrial após cirurgia cardíaca

Abstract: Objective: Corticosteroids decrease side effects after noncardiac elective surgery. A randomized, double blinded, placebo-controlled study was plan to test the hypothesis that standard doses of dexamethasone (6X2) would decrease the incidence of atrial fibrillation (AF) following cardiac surgery.Methods: A total of 185 patients undergoing coronary revascularization surgery were enrolled in this clinical study. The anesthetic management was standardized in all patients. Dexamethasone (6 mg/ml) or saline (1 ml) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Eleven studies [22,27,37,38,[45][46][47][48][49][50][51] used low-dose corticosteroids with the remaining 51 studies administered high-dose corticosteroids. There was no significant interaction between high-and low-dose corticosteroid and the incidences of myocardial or pulmonary adverse events and surgical site infection.…”
Section: Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies [22,27,37,38,[45][46][47][48][49][50][51] used low-dose corticosteroids with the remaining 51 studies administered high-dose corticosteroids. There was no significant interaction between high-and low-dose corticosteroid and the incidences of myocardial or pulmonary adverse events and surgical site infection.…”
Section: Subgroup Analysesmentioning
confidence: 99%
“…A previous systematic review and meta-analysis published in 2011 found that corticosteroids were not associated with any significant reduction in clinically important adverse outcomes from heart surgery [19]. Since that review was published, 8 randomized controlled trials (RCTs) including 2 trials [20,21] with large population sample sizes have been published [20][21][22][23][24][25][26][27]. Thus, an updated systematic review and meta-analysis is warranted to summarize the current understanding of the use of corticosteroids in patients undergoing heart surgery with CPB.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is a common complication after cardiac surgery, affecting about 10% to 40% of patients undergoing Coronary Artery Bypass Grafting (CABG) [ 1 - 3 ] . This arrhythmia occurs most frequently in the first five days of the postoperative period, peaking between 24 and 72 hours, being uncommon after the first week [ 3 , 4 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative atrial brillation (POAF) is a common arrhythmia that occurs 15-40% after CABG and may worsen the prognosis of patients in the intensive care unit (ICU) (Abbaszadeh, Khan, et al 2012, Bohatch Júnior, Matkovski, et al 2015, Gamst, Christiansen, et al 2015. This arrhythmia occurs most commonly 1-5 days after surgery, peaks from 24 to 72 hours, and decreases within 4 to 7 days after surgery (Silva, Lima, et al 2010;Peretto, Durante, et al 2014).…”
Section: Introductionmentioning
confidence: 99%